The effects of tailor-made flood risk advice for homeowners in Flanders, Belgium. Issue 5 (4th July 2019) - Davids, Peter; Boelens, Luuk; Tempels, Barbara
ABSTRACT: Although flood risk management is traditionally regarded as a governmental responsibility, homeowners in Flanders (Belgium) have a crucial role in flood risk reduction. With this in mind, the Flanders Environment Agency executed a pilot study in which homeowners were offered free tailor-made advice on floodproofing. To evaluate the advice, we conducted interviews and a survey of the participating homeowners. On this basis we conclude that, to improve the homeowner's contribution towards more effective flood-resilient (peri-)urban areas, there is a need for a more relational approach with other stakeholders.